Dampak Implementasi Program Smart Kampung di Kabupaten Banyuwangi - Abdul Hakim; Betty Silfia Ayu Utami; Maziyah Mazza Basya (OECONOMICUS Journal of Economics, 2022)
This study aims to analyze the impact of the implementation of the "Smart Kampung" program on economic aspects and public services in Banyuwangi. Smart kampung provides space for government work programs in all fields in an integrated and integrated manner between one government agency and other governments.The impact of the smart village program on the economic aspect in the 10 villages that became the smart village pilot project in Banyuwangi district is different. The village government is required to support the implementation of the smart village program so that the smart village program has a positive impact on the economy of its village residents, namely by producing innovative programs by encouraging productive economic activities, creative economic activities.